THE PLANNING STRATEGY OF ISLAMIC EDUCATION TEACHERS IN MADRASAH TSANAWIYAH - Ahmad Syarif (INCARE, International Journal of Educational Resources, 2023)
Teachers are the key element in educational institutions. Teachers have a responsibility to maximize the learning process to achieve the expected learning goals. The purpose of this study is to determine how PAI (Islamic Education) teachers' learning strategies at Madrasah Tsanawiyah DDI Patobong, under the auspices of Pondok Pesantren Manbaul Ulum DDI Patobong. The research approach used in this study is qualitative (field research). Data collection techniques used in this study include document analysis, observation, and interviews. In this research, data validity testing emphasizes on credibility test. The results show that lesson planning applied by Islamic Education teachers at Madrasah Tsanawiyah DDI Patobong merely involves preparing an implementation plan based on the teacher's guidebook. Some Islamic Education teachers at Madrasah Tsanawiyah DDI Patobong have been able to organize their teaching by structuring teaching materials and summarizing the content of lessons.